Capitalism and democracy - the origin, the causes of the crisis and the possibilities of their overcoming in the work of Jürgen Kocka and Niall Ferguson - Baščarević, Ivan M. (Sociološki pregled, 2018)
The paper discusses the theories of Jürgen Kocka and Niall Ferguson about the emergence of capitalism and democracy, the causes of the crisis and the possibilities of their overcoming. The author found the inspiration for writing this text in the books The History of Capitalism (Jürgen Kocka) and The Great Degeneration - How Institutions Decay and Economies Die (Niall Ferguson). Why? Firstly, we are witnessing a time in which, along with all theoretical and ideological concepts and criticisms, an adequate alternative to capitalism as a socio-economic model has not been found yet. Secondly, the evident social reasons reﬂected in the growing social inequalities, poverty, the rise of crime and corruption, the oligarchy of political and economic elites, the weakening of the institutions of the system, the “collapse” of the welfare state, the reduction of human and civil liberties and other, indicate the actuality of studying the contemporary concept of capitalism and democracy. Tirdly, both books appeared almost at the same time (in Serbia in 2016), oﬀering, although from diﬀerent theoretical orientations, the answers to the causes of the emergence of these problems and the possibilities of their overcoming. Finally, the author of this text considered it necessary to modestly contribute to the interpretation and explanation of capitalism in theory and social practice through a detailed analysis and by approaching both theoretical conceptions, noting their diﬀerences and similarities. Keywords: Jürgen Kocka, Niall Ferguson, historical sociology, capitalism, democracy, emergence, causes of crisis, possible solutions.